2012
DOI: 10.1111/j.1365-2990.2011.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse form of dysembryoplastic neuroepithelial tumour: the histological and immunohistochemical features of a distinct entity showing transition to dysembryoplastic neuroepithelial tumour and ganglioglioma

Abstract: Immunoreactivity for CD34 and nestin characterizes the dDNT and helps to distinguish it from other lesions associated with epilepsy. Histological evidence indicative of transition of dDNT to other forms of DNT and ganglioglioma suggests that dDNT might be an early histogenetic form of these glioneuronal tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 35 publications
1
30
2
Order By: Relevance
“…Higher expression levels of nestin, MAP2 and CD34, stem cell markers, in nonspecific rather than simple or complex DNTs suggests an earlier developmental origin of the nonspecific DNTs. 8,30 Because DNTs share CD34 expression, BRAF V600E mutations, and chromosomal copy number profiles with gangliogliomas, and occurrence of composite tumors with ganglioglioma and DNT, both tumors may represent different morphological variants of the same tumor entity. …”
Section: Histogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…Higher expression levels of nestin, MAP2 and CD34, stem cell markers, in nonspecific rather than simple or complex DNTs suggests an earlier developmental origin of the nonspecific DNTs. 8,30 Because DNTs share CD34 expression, BRAF V600E mutations, and chromosomal copy number profiles with gangliogliomas, and occurrence of composite tumors with ganglioglioma and DNT, both tumors may represent different morphological variants of the same tumor entity. …”
Section: Histogenesismentioning
confidence: 99%
“…5 However, several studies demonstrated three histologic forms of DNTs under the different terms "multinodular, solitary nodular, and diffuse" or "simple, complex, and diffuse." [6][7][8] The frequent immunoreactivity of CD34, nestin, and microtubule-associated protein 2 (MAP2) 9 and the identification of BRAF V600E mutation in nonspecific DNTs 10 suggest that DNTs exhibit a broad spectrum of histopathology from simple to nonspecific forms.A large series of DNTs demonstrated intrinsic epileptogenicity of DNTs in three histologic subtypes by intralesional recordings and simple and complex types showed localization of the epileptogenicity to the tumor, but non-specific temporal DNTs showed more extensive areas with the epileptogenicity. In their series, FCD was found in approximately two-thirds of patients with DNTs and was more common in nonspecific (85%) than in complex types (47%).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The last form was created based on the statement that the diffuse form of DNT corresponds to a non-specific variant [8,19,29]. However, the diagnosis and definition of the non-specific type of DNT is controversial.…”
Section: Histopathologymentioning
confidence: 99%